Influence of the Professional Values on Providing Social Work Suport - Sivreva, Antoniya; Benkova, Krasimira (Socialinė teorija, empirija, politika ir praktika, 2024)
This article aims at examining the degree of influence of the professional values with regards to activities related to providing support among social work professionals in Bulgaria. In the survey which was conducted on a voluntary and anonymous basis, 204 social work professionals from the Stara Zagora Region took part. The WIS/SVP method – Scale for assessing professional values was applied. Examined were the influencing factors referring to professional values and provision of social support. Found out were influencing factors between most of the professional values and the desire to provide assistance and readiness for participation in activities related to providing support. The obtained results place professional values as one of the factors determining the trend for providing assistance and participation in support activities in the field of social work in Bulgaria.